The reality of endowment management in emerging Saudi universities to finance university education from the point of view of academic leaders and employees - Mohammed, Saeed Omair (Journal of Educational and Psychological Sciences, 2024)
The aim of the study was to identify the current role of endowment management in emerging Saudi universities in financing higher education, based on the perspectives of stakeholders, and to explore how to enhance this role. The study also aimed to uncover statistically significant differences based on variables such as gender, educational qualification, years of experience, and number of training courses attended. To achieve these objectives, a purposive sample of endowment leaders in government universities in Saudi Arabia was used, with a total of 296 participants. The study employed a descriptive survey methodology.The results of the study indicated that the current state of endowment management in emerging Saudi universities for financing higher education was at a moderate level, with statistically significant differences favoring females with 10 or more years of experience and 11 or more training courses attended.One of the recommendations put forward emphasized the need to focus on the development and enhancement of university endowment management in emerging universities through partnerships, providing training and development opportunities, and strengthening financial oversight. Additionally, improving work methods in endowment management and conducting further research were highlighted. Developing university endowment management can contribute to enhancing its efficiency, increasing its ability to achieve its goals, and aligning with the vision of Saudi Arabia 2030.
Keywords: Endowment; Endowment Management; Emerging Universities; Financing Higher Education